Reimagining Arab political identity - Hawa, Salam, author.
1 online resource.
Keywords: "This book discusses the idea that Arab cultural and political identity has been suppressed by centuries of dominance by imperial outsiders and by religious and nationalist ideologies with the result that present day Arab societies are characterised by a crisis of identity where fundamentalism or chaos seem to be the only available choices. Tracing developments from pre-Islamic times through to the present, the book analyses the evolution of Arab political identity through a multi-layered lens, including memory and forgetting, social and cultural norms, local laws, poetry, dance, attitudes to women, foreigners and animals, ancient historical narratives and more. It argues that Arab societies have much to gain by recovering the "happy memory" of Arab culture as it was before being distorted"--